Interaction Between Micropollutants and Degradative Biofilm Communities : Basis for a Biomimetic Approach to Water Treatment - Kenchenten, Kirsten (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.